Immobilisation and flow chemistry: tools for implementing biocatalysis. Issue 87 (12th October 2021) - Coloma, José; Guiavarc'h, Yann; Hagedoorn, Peter-Leon; Hanefeld, Ulf
Abstract : The application of immobilised enzymes in flow allows for process intensification, reduced reactor volumes and improved safety. Abstract : The merger of enzyme immobilisation and flow chemistry has attracted the attention of the scientific community during recent years. Immobilisation enhances enzyme stability and enables recycling, flow chemistry allows process intensification. Their combination is desirable for the development of more efficient and environmentally friendly biocatalytic processes. In this feature article, we aim to point out important metrics for successful enzyme immobilisation and for reporting flow biocatalytic processes. Relevant examples of immobilised enzymes used in flow systems in organic, biphasic and aqueous systems are discussed. Finally, we describe recent developments to address the cofactor recycling hurdle.